Standard catalog of world paper money - Schmidt, Tracy L. (Iola, Wisconsin : Krause, 2018)
Featuring the insight and experience of a worldwide network of numismatics experts, the 24th edition of the Standard Catalog of World Paper Money, Modern Issues, provides the most comprehensive and complete reference to world bank notes issued since 1961.
ne 23/08/2022
Loans
Keywords: Paper money